US financial shocks and the distribution of income and consumption in the UK - Haroon Mumtaz; Konstantinos Theodoridis (Cardiff University, Cardiff Business School, 2017)
We show that US financial shocks have an impact on the distribution of UK income and consumption. Households with higher income and higher levels of consumption are affected more by this shock than households located towards the lower end of these distributions. An estimated multiple agent DSGE model suggests that the heterogeneity in the household responses can be explained by the different levels of access to financial markets. We find that this heterogeneity magnifies the effect of this shock on aggregate output.
Keywords: D31; E32; E44; 330; FAVAR; DSGE model; Financial Shock